What is the impact of educational systems on social mobility across Europe? A comparative approach - Abrantes, Pedro (2012)
Education is reasonably expected to enhance intergenerational social mobility. However, the extent to which educational systems foster or otherwise constrain social mobility remains controversial. In this paper, data from the European Social Survey covering 22 countries is analysed in order to assess social mobility in the second half of the 20th Century. Variation across five cohesive regional clusters is examined in detail. Results confirm increasing rates of social mobility in Europe and their close relation to massive structural shifts. The erosion of the education-occupation linkage presents a current threat to this trend. Considering formal credentials only, the most equalitarian educational systems are to be found in the United Kingdom and Ireland, but their ability to allocate individuals in the occupational structure is lower than in the other regions. Scandinavian systems show higher chances of social mobility through education, while Mediterranean systems present lower fluidity rates in both the background-education link (like Eastern European countries) and the education-occupation link (like the UK & Ireland). Gender and migration are identified as key factors to explain these differences.